2016
DOI: 10.3390/ijerph13100993
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the Nematode Caenorhabditis elegans to Evaluate the Adverse Effects of Epoxiconazole Exposure on Spermatogenesis

Abstract: There is increasing evidence that epoxiconazole exposure can affect reproductive function, but few studies have investigated adverse effects on spermatogenesis. The nematode Caenorhabditis elegans (C. elegans) was used in our study to assess effects of epoxiconazole on spermatogenesis in male nematodes after 48 h of exposure to concentrations of 0.1, 1.0, or 10.0 μg/L. The results demonstrated that epoxiconazole exposure affected spermatogenesis, decreasing the number of total germ cells, mitotic cells, meioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…However, 20 µM of Tb reduced human colon HCT116 cells line’ viability [43] . Epoxiconazole exposure (from 0.1 to 100 µg/L for 48 h) in the germ cells of C. elegans led to the arrest of cell proliferation [37] whereas higher doses (6.25 and 75 µM of E) stimulated the proliferation of MCF-7 BUS, a human breast cancer cells line [34] . Thus, the effects of these triazoles are dependent on the type of cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, 20 µM of Tb reduced human colon HCT116 cells line’ viability [43] . Epoxiconazole exposure (from 0.1 to 100 µg/L for 48 h) in the germ cells of C. elegans led to the arrest of cell proliferation [37] whereas higher doses (6.25 and 75 µM of E) stimulated the proliferation of MCF-7 BUS, a human breast cancer cells line [34] . Thus, the effects of these triazoles are dependent on the type of cells.…”
Section: Discussionmentioning
confidence: 99%
“…on C. elegans behavior, development and neural function. More recently, researchers evaluated the effects of triazole fungicides, particularly epoxiconazole, on nematode growth and reproduction [18] and determined that spermatogenesis is inhibited by epoxiconazole. These findings agree with reports of endocrine-disrupting effects of this family of fungicides in rats and birds [17,70,71].…”
Section: Discussionmentioning
confidence: 99%
“…One recent study demonstrated edema and necrosis of circular and longitudinal muscle layers in earthworms exposed to tebuconazole for 14 days [16]. Further, epoxiconazole, a commonly applied triazole, acts as a male reproductive toxicant in rats [17] and damaged spermatogenesis in C. elegans [18]. Pursuing studies using C. elegans is a very useful and important avenue of research.…”
Section: Azole Fungicidesmentioning
confidence: 99%
“…Thereby C. elegans indicated similar sensitivity than D. magna and the redworm Eisenia fetida regarding several of the above cited metals(Queirós et al 2019) Lopes et al 2008),. interference with biochemical signaling pathways (e.g.,Li et al 2016) or cumulative effects(Martin et al 2009). Several PPCPs were reported for DART in C. elegans such as EE2(Höss and Weltje 2007), nicotine (e.g.,Smith et al 2013), piperazine analogs(Racz et al Yu et al 2011, Liu et al 2013 or the antimicrobial agents triclocarban and triclosan (LOECs of 10-100 µg/L respectively,Lenz et al 2017, . The ECs of triclocarban and triclosan were thereby similar than to those of D. renio embryos(Sreevidya et al 2018).…”
mentioning
confidence: 99%
“…epoxiconazole (LOEC of 0.1 µg/L,Li et al 2016) or lindane (at 1-100 ng/L,Yu et al 2020). DART of other pesticides thereby included transgenerational effects (e.g.,  Several environmental hormones and EDCs were positively assessed for DART in C. elegans.…”
mentioning
confidence: 99%